2017
DOI: 10.1038/s41598-017-05560-1
|View full text |Cite
|
Sign up to set email alerts
|

MiR-30a targets IL-1α and regulates islet functions as an inflammation buffer and response factor

Abstract: Diabetes is an inflammatory disease. Inflammation plays an important role in islet functions. However, the exact mechanisms by which inflammation affects islet functions remain unclear. In this study, we investigated the regulatory effects of miR-30a on inflammation and islet functions. The results indicate that miR-30a serves as an inflammation-resolving buffer factor by targeting interleukin 1a (IL-1α) in immune cells and in islet cells, which might play an important role in inflammation homeostasis. miR-30a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…Finally, we searched the literature for miRNAs similar to miR-222, which were reported to be induced due to targeting of a shorter minor isoform induced by LPS. We found that miR-30a-5p which is annotated as a 22 nt isoform in miRBase, was previously shown to be induced in mouse RAW267.4 macrophages stimulated with 24-h LPS treatment, by stem-loop Taqman RT-qPCR (Jiang et al 2017). Nonetheless, the overall miR-30a-5p levels were not induced by bacterial products in human macrophages and mouse BMDMs/BMDCs in our analyses, since the prevalent isoform of this miRNA, the 24 nt, was not induced (and rather modestly decreased for instance in human and mouse macrophages) ( Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Finally, we searched the literature for miRNAs similar to miR-222, which were reported to be induced due to targeting of a shorter minor isoform induced by LPS. We found that miR-30a-5p which is annotated as a 22 nt isoform in miRBase, was previously shown to be induced in mouse RAW267.4 macrophages stimulated with 24-h LPS treatment, by stem-loop Taqman RT-qPCR (Jiang et al 2017). Nonetheless, the overall miR-30a-5p levels were not induced by bacterial products in human macrophages and mouse BMDMs/BMDCs in our analyses, since the prevalent isoform of this miRNA, the 24 nt, was not induced (and rather modestly decreased for instance in human and mouse macrophages) ( Fig.…”
Section: Resultsmentioning
confidence: 88%
“…LH exhibited anti-inflammatory effects in LPS-induced mice [ 19 ] and inhibited ROS production in LPS- and PMA-induced THP-1 cells. LPS and PMA increased ROS production in monocytes and macrophage cells [ 20 , 21 ]. NAFLD is associated with macrophage recruitment and consequent inflammation after adipocyte enlargement [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of immunity, both miR-148a-3p and miR-30a-5p modulate inflammation by repressing NF-κB signaling in macrophages and respective pro-inflammatory consequences [82, 83]. It was shown that the use of miRNAs mimicking miR-30a significantly down-regulates the expression levels of IL-1α, IL-6 and TNF-α mRNAs in LPS-stimulated macrophages [82].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of immunity, both miR-148a-3p and miR-30a-5p modulate inflammation by repressing NF-κB signaling in macrophages and respective pro-inflammatory consequences [82, 83]. It was shown that the use of miRNAs mimicking miR-30a significantly down-regulates the expression levels of IL-1α, IL-6 and TNF-α mRNAs in LPS-stimulated macrophages [82]. In our study, miR-148a-3p and miR-30a-5p were dramatically down-regulated, which is consistent with previous reports showing that in mice, primary AE is characterized by an initial acute inflammatory Th1 immune response which then gradually shifts to a Th2 response due to an immunomodulatory down-regulation effect presumably mediated by the E. multilocularis larvae [8, 84].…”
Section: Discussionmentioning
confidence: 99%